Pengaruh Kompetensi dan Motivasi Kerja Terhadap Kinerja Karyawan Bagian Produksi Pada PT Samkyung Jaya Garment Ungaran - Rofi’atun Nashiroh; Amsar Amsar (LPPM Universitas 17 Agustus 1945 Semarang, 2022)
This study aims to determine and analyze the effect of competence and work motivation on employee performance. In this study, the population used was 1,000 employees of the production division of PT. Samkyung Jaya Garment Ungaran which consists of 554 female workers and 446 male workers. The number of samples used were 91 respondents with probability sampling technique. Methods of data collection using questionnaires and literature study. The research analysis used multiple linear regression analysis. The results showed that competence had a positive and significant effect on employee performance. This result shows that if competence is improved, it will be followed by an increase in employee performance. Work motivation has a positive and significant impact on employee performance. This result shows that if work motivation is increased, it will be followed by an increase in employee performance.